2021
DOI: 10.1111/desc.13095
|View full text |Cite
|
Sign up to set email alerts
|

Development of directed and random exploration in children

Abstract: Children are natural born explorers. While exploration and active learning are quintessential features of development and maturation, they also pose fundamental challenges to children and adults alike. In particular, efficiently searching for information and rewards requires balancing the dual goals of exploring unknown options to learn something new, and exploiting familiar options to obtain known rewards. At a restaurant, should you go with your usual favorite or should you try the chef's latest creation? As… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 69 publications
5
71
1
Order By: Relevance
“…higher payout). This is in line with the conceptualization of random exploration as an inferior exploration strategy (Meder et al, 2021), which requires only little cognitive resources and is implemented in a simpler fashion into cognitive and neural processes by using neural or environmental noise to randomize choice (Zajkowski et al, 2017). Directed exploration, on the other hand, as reflected in the exploration bonus parameter 𝜑, showed an inverted-U-shaped association with task performance.…”
Section: Implications For Empirical Researchsupporting
confidence: 81%
See 2 more Smart Citations
“…higher payout). This is in line with the conceptualization of random exploration as an inferior exploration strategy (Meder et al, 2021), which requires only little cognitive resources and is implemented in a simpler fashion into cognitive and neural processes by using neural or environmental noise to randomize choice (Zajkowski et al, 2017). Directed exploration, on the other hand, as reflected in the exploration bonus parameter 𝜑, showed an inverted-U-shaped association with task performance.…”
Section: Implications For Empirical Researchsupporting
confidence: 81%
“…Random exploration has low computational costs but does not lead to optimal performance. Directed exploration is a more elaborate strategy involving more computational costs and leading to better performance (Meder et al, 2021;Wilson et al, 2014). Another phenomenon occurring in explore-or-exploit situations is perseveration, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also provide the foundation of active learning strategies used to adaptively sample high-dimensional search spaces, for instance in material sciences (Lookman et al, 2019), drug discovery (Murphy, 2011), or learning of protein interactions (Mohamed et al, 2010). How humans search large decision spaces has also been addressed in recent psychological research (Meder et al, 2021;Schulz et al, 2019;Wu et al, 2018).…”
Section: What Makes a Good Query?mentioning
confidence: 99%
“…This attentional capture can be characterized in terms of information gain (Kidd, Piantadosi, & Aslin, 2012), with infants showing the most attention to situations of intermediate visual complexity, supposedly to avoid wasting cognitive resources trying to process overly simple or overly complex events (Schmidhuber, 2010). Along these lines, a growing body of work has shown that children are more likely to explore when presented with confounded (L. E. Schulz & Bonawitz, 2007) or unexpected evidence (Bonawitz, van Schijndel, Friel, & Schulz, 2012), that they seek out uncertainty reduction more eagerly than adults (Meder, Wu, Schulz, & Ruggeri, 2020;E. Schulz, Wu, Ruggeri, & Meder, 2019) and are sensitive to the potential information gain of different actions (Jirout & Klahr, 2012;Ruggeri, Sim, & Xu, 2017;Ruggeri, Swaboda, Sim, & Gopnik, 2019).…”
mentioning
confidence: 99%